Synthesis and area-wide validation of adaptable IPM technology and its economic analysis for bitter gourd (Momordica charantia) in a farmers' driven approach - HALDER, JAYDEEP; SARDANA, H R; KRISHNAN, NAGENDRAN; PANDEY, M K; BHAT, M N; BANERJEE, KAUSHIK (The Indian Journal of Agricultural Sciences, 2018)
Field experiment was conducted in bitter gourd (Momordica charantia L.) during 2014-16 at Varanasi, Mirzapur and Deoria districts of eastern Uttar Pradesh with a view to study the validation, economic viability and feasibility of adaptable and rational IPM technology in a farmers led approach.The IPM technology that synthesized for bitter gourd crop comprised seed treatment with Trichoderma viride @ 5g/kg of seed; need based spraying of azadirachtin (0.03%) based neem insecticide @ 10 ml/l for hadda beetle; installation of cue lure traps (MAT) for fruit flies @ 10/acre; raking of soil for exposing fruit fly pupae to sunlight and predatory fauna and removal of associated weeds, need based application of Bacillus thuringiesnsis @ 2 g/l against cucumber moth, Diaphania indica; Imidacloprid 17.8SL @ 1 ml/l of water for whitefly; systemic fungicide Cymoxanil l8 WP+Mancozeb 64 WP @ 2.5 g/l against downymildew were found very effective in reducing the incidence of pests and minimizing the yield losses. The adoption of IPM technology during the three years, apart from lowering the incidence of major pests, resulted in reducing the number of chemical sprays to 7-9 from 21-25 in non-IPM fields in a season with higher bitter gourd yields of 18, 16.5 and 18.7 tonnes/ha in IPM and 14.4, 11.8 and 15.1 tonnes/ha in non-IPM fields and with marginally higher cost benefit (C:B) ratio of 1:2.19, 1:2.58 and 1:3.01 in IPM than 1:1.70, 1:1.78 and 1:2.30, respectively in non-IPM for the three consequitive years. There was a net income increase IPM fields over farmers' practice fields. On an average, IPM farmers had an average higher net return of Rupees 2.37 lakh/ha with C:B ratio of 1:2.59 as compared to the non-IPM farmers with net return of Rupees 1.49 lakh/ha with a B:C ratio of 1:1.93.